Synergistic Neuropsychopharmacological Potential of Peganum harmala and Cucurbita pepo: A Narrative Review of Mechanisms, Evidence, and Toxicological Cautions - Albukhari, Abdullah Faisal (Pharmacognosy Reviews)
Neuropsychiatric conditions, including depression and anxiety, pose significant challenges to global health. These issues are often intensified by the limitations of existing pharmacological treatments, which may have delayed effects, incomplete responses, and various side effects. Consequently, there is a growing interest in herbal therapies that provide diverse neuropharmacological benefits. This narrative review aims to critically analyze the potential synergistic interaction between Peganum harmala and Cucurbita pepo in influencing neurobiological pathways associated with mood disorders, drawing on current phytochemical, pharmacological, and preclinical research. A comprehensive literature review was conducted utilizing PubMed, Scopus, and Google Scholar to identify studies-both in vitro and in vivo-as well as mechanistic investigations related to P. harmala and C. pepo. The emphasis was placed on serotonergic modulation, antioxidant effects, GABAergic regulation, and mitochondrial support. P. harmala is known to contain β-carboline alkaloids (such as harmine and harmaline) that inhibit MAO-A enzymes, thereby increasing monoamine levels and modulating GABA-A receptors. On the other hand, C. pepo contributes tryptophan, magnesium, and antioxidants that aid serotonin production and offer neuroprotective benefits. While both substances demonstrate antidepressant- and anxiolytic-like effects individually in animal models, their combined use has not yet been investigated. Concerns about toxicity primarily relate to P. harmala's potential neurotoxicity and interactions with serotonergic systems; however, C. pepo is generally regarded as safe with a substantial safety margin. Although theoretical synergy exists based on mechanistic evidence, direct empirical validation is currently lacking. The suggested combination of Peganum harmala and Cucurbita pepo presents an intriguing multi-target approach for mood management. Nonetheless, the lack of clinical trials, data on in vivo synergy, and assessments of human safety restricts immediate application of this strategy. Future research should emphasize experimental validation along with toxicological modeling and AI-assisted formulation techniques to advance this promising phytotherapeutic idea into practical clinical use.
Keywords: Peganum harmala; Cucurbita pepo; β-carbolines; MAO-A Inhibition; Tryptophan; Phytotherapy; Neuropsychiatric Disorders; Depression; Anxiety; Antioxidant; GABAergic Modulation; Serotonin; Herbal synergy; Neuroprotection